Design, implementation,and characterization of JFET-based color sensors - Mo,Yajie (Nanyang Technological University, 2023)
Optoelectronic sensors can convert optical signals into electrical signals. Its operating principle is based on the photoelectric effect. Optoelectronic sensors are widely used in industrial applications because of their non-contact, fast response and high reliability. JFETs are attractive new alternative image sensors because of their good optoelectronic properties and low cost. This project deals with a new type of image sensor based on the junction field effect transistor (JFET), and its electrical and optical properties. The image sensor features the ability to simultaneously absorb red, green, and blue light in different areas and generate the corresponding photocurrents.